2005
DOI: 10.1111/j.1365-2761.2004.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

White tail disease of the giant freshwater prawn, Macrobrachium rosenbergii: separation of the associated virions and characterization of MrNV as a new type of nodavirus

Abstract: White tail disease of the farmed freshwater prawn, Macrobrachium rosenbergii, is the cause of mortalities in the French West Indies, China and India. Two different sized particles, both developing in the cytoplasm of target cells, are found associated with diseased animals. These two viruses were separated, purified and subsequently characterized. The larger one, called MrNV, is icosahedral in shape and 27 nm in diameter. Its genome is composed of two fragments of linear single-stranded RNA (ss-RNA), of 2.9 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 18 publications
1
71
0
Order By: Relevance
“…Amino acid sequencing of CP-17 and CP-16 clearly indicated that both polypeptides were encoded by the same reading frame and that CP-16 was a truncated form of CP-17, lacking the first 11N-terminal amino acids and it is worthwhile mentioning that the N-terminal end of both polypeptides is methionine. CP-16 was not a degraded form of CP-17 as both polypeptides were found in equimolar ratio and analysis was carried out by directly dissolving the virus particles in Laemmli buffer [2]. Besides, the ATG codon of CP-16 is localized in a favorable Kozak context as the ATG codon of CP-17 (7 out of 11 nucleotides matching with the Kozak consensus sequence).…”
Section: Causative Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid sequencing of CP-17 and CP-16 clearly indicated that both polypeptides were encoded by the same reading frame and that CP-16 was a truncated form of CP-17, lacking the first 11N-terminal amino acids and it is worthwhile mentioning that the N-terminal end of both polypeptides is methionine. CP-16 was not a degraded form of CP-17 as both polypeptides were found in equimolar ratio and analysis was carried out by directly dissolving the virus particles in Laemmli buffer [2]. Besides, the ATG codon of CP-16 is localized in a favorable Kozak context as the ATG codon of CP-17 (7 out of 11 nucleotides matching with the Kozak consensus sequence).…”
Section: Causative Organismsmentioning
confidence: 99%
“…Two viruses namely Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus-like particle (XSV) are responsible for WTD [2]. MrNV is a small, icosahedral, non-enveloped particle, 26-27 nm in diameter (Fig.…”
Section: Causative Organismsmentioning
confidence: 99%
“…MrNV is a nonenveloped, icosahedral virus with a diameter of 26-27 nm and a genome comprised of two pieces of positive-sense ssRNA. RNA 1 is 3202 bp in length and encodes the RdRp, whereas RNA 2 is 1175 bp in length and encodes a viral capsid protein of 43 kDa [96,101] . Extra small virus (XSV) is usually associated with MrNV.…”
Section: Mrnv Nodavirus and Extra Small Virusmentioning
confidence: 99%
“…Its genome is composed of two fragments of linear single-stranded RNA (ss-RNA), of 2.9 and 1.3 kb, respectively and its capsid is made up of a single polypeptide of 43 kDa [2]. MrNV is associated with a small virus, XSV, a non-enveloped icosahedral virus, 15 nm in diameter [10].…”
mentioning
confidence: 99%
“…The genome is in sense orientation, with a short poly (A) tail at the 3 0 -end. The genome has an ORF of 522 nucleotides coding for a 174 amino acid polypeptide of 17 kDa and a truncated protein of 16 kDa lacking the first 11 N-terminal amino acids [2,10].…”
mentioning
confidence: 99%